LIVING IN TWO DIFFERENT CULTURES AMERICA AND ARAB IN CARMEN BIN LADIN'S INSIDE THE KINGDOM (2004): A SOCIOLOGICAL APPROACH - FAUZIA, DIAZ RANIRI (2011)
The major problem of this study is how is the writer manages herself to live in two different cultures between western and Eastern. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on sociological analysis In analyzing inside the kingdom, the writer uses qualitative method and sociological approach. The data sources consist of primary data and secondary data sources. The primary data source is the novel inside the kingdom itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and sociological. The method of the data collection is descriptive analysis. The outcomes of the study show the following conclusions. First, from the structural elements, shows that the writer wants to convey her idea about how she overcomes her problem about difference culture which is faced by herself during her marriage. Second, based on sociological approach, she still holds of her culture and tries to survive to live in Arab. Saudi Arabia follows the Wahabi custom in their daily life.